Le désir et le désert. L’écriture érotique du deuil dans Corps mémorable de Paul Éluard (TEST Ticontre. Theory Text Translation, 2018)
In his analysis of modern poetry’s metamorphoses, Claude Vigée underlines a new poetic function of erotic desire in post-Baudelairean poetry: “Such is the task assigned from now on to modern Eros: to disguise the abyss”. Thus, the link between Eros and Thanatos, inherited from a literary tradition rooted in the courtly poetry, turns out to be a specific feature of poetic modernity. In Paul Éluard’s poetics, carnal desire is systematically associated with the expression of melancholy: one can think of Capitale de la douleur, but also of Le dur désir de durer, and especially of Corps mémorable, one of the most erotic collections by the poet. Placed jointly under the sign of the mourning of Nusch Éluard and an open relationship – including a couple of friends, Alain and Jacqueline – Corps mémorable mixes the imagination of death with the imagination of pleasure within a melancholic and modern figuration of Eros. We aim to analyse this text as a sensual example of writing the mourning, in order to study the convergence of eroticism and melancholy. In the aesthetics of Corps mémorable, « les baisers résurrecteurs » represent the physical redemption through carnal intimacy, whereas melancholy appears as macabre eroticism. Therefore, the two-fold experience of the desert – which refers to existential unrest in the vocabulary of Éluard’s poetry – and that of desire highlights a properly erotic melancholy: « Un baiser encore un baiser un seul / Pour ne plus penser au désert ».In his analysis of modern poetry’s metamorphoses, Claude Vigée underlines a new poetic function of erotic desire in post-Baudelairean poetry: “Such is the task assigned from now on to modern Eros: to disguise the abyss”. Thus, the link between Eros and Thanatos, inherited from a literary tradition rooted in the courtly poetry, turns out to be a specific feature of poetic modernity. In Paul Éluard’s poetics, carnal desire is systematically associated with the expression of melancholy: one can think of Capitale de la douleur, but also of Le dur désir de durer, and especially of Corps mémorable, one of the most erotic collections by the poet. Placed jointly under the sign of the mourning of Nusch Éluard and an open relationship – including a couple of friends, Alain and Jacqueline – Corps mémorable mixes the imagination of death with the imagination of pleasure within a melancholic and modern figuration of Eros. We aim to analyse this text as a sensual example of writing the mourning, in order to study the convergence of eroticism and melancholy. In the aesthetics of Corps mémorable, « les baisers résurrecteurs » represent the physical redemption through carnal intimacy, whereas melancholy appears as macabre eroticism. Therefore, the two-fold experience of the desert – which refers to existential unrest in the vocabulary of Éluard’s poetry – and that of desire highlights a properly erotic melancholy: « Un baiser encore un baiser un seul / Pour ne plus penser au désert ».Dans son analyse des métamorphoses de la poésie moderne, Claude Vigée repère une nouvelle fonction poétique du désir érotique chez les poètes post-baudelairiens : « Telle est donc la tâche assignée désormais à l’Éros moderne : jeter un déguisement sur l’abîme ». Le lien entre Éros et Thanatos, hérité d’une filiation littéraire qui s’enracine dans la poésie courtoise, semble ainsi cristalliser une spécificité de la modernité poétique. Dans toute la poétique de Paul Éluard, le désir charnel est intimement associé à l’expression de la mélancolie : nous pensons à Capitale de la douleur, mais aussi au Dur désir de durer, et surtout au Corps mémorable, l’un des recueils les plus érotiques du poète. Placé conjointement sous le signe du deuil de Nusch Éluard et d’une relation à trois – que le poète partage avec un couple d’amis, Alain et Jacqueline – Corps mémorable entremêle l’imaginaire de la mort à celui du plaisir pour dévoiler un Éros mélancolique moderne. Nous proposons de relire ce texte à l’aune de l’écriture sensuelle du deuil afin d’étudier la convergence entre érotisme et mélancolie. Dans l’esthétique de Corps mémorable, les « baisers résurrecteurs » figurent la rédemption physique par l’intimité charnelle, tandis que la mélancolie se manifeste sous la forme d’un érotisme macabre. Aussi, la double expérience du désert – qui renvoie à la détresse existentielle dans le vocabulaire éluardien – et du désir met à jour une mélancolie proprement érotique : « Un baiser encore un baiser un seul / Pour ne plus penser au désert ».